Effect of low temperature blanching, cysteine-HCI, N-acetyl-L-cysteine, Na metabisulphite and drying temperatures on the firmness and nutrient content of dried carrots - Mohamed, Suhaila; Hussein, Rosli (Wiley, 1994)
Low temperature long time (LTLT) blanching (70C for 20 min) together with calcium treatment can be used to significantly improve the texture of rehydrated dried carrots when compared to high temperature short time (HTST) blanching (100C for 3 min). LTLT blanching allows pectin methyl esterase to deesterify pectin which can then react with calcium to form salt bridges. 0.3% L-cysteine-HCl was found to be most effective in preventing ascorbic acid loss and obtaining a product with the highest rehydration ability, compared to pretreatments with 0.3% N-acetyl-L-cysteine and 0.1% sodium metabisulphite. On the other hand 0.1% sodium metabisulphite was most effective in preserving the carotenoids content of dried carrots. Ascorbic acid and rehydration ability were more adversely affected by long drying time than high drying temperature, while carotenoids were more sensitive to high drying temperature than drying time. Hence, 60C drying temperature was good for ascorbic acid and rehydration ability, while 40C drying temperature was good for carotenoid and color of dried carrots.